2006
DOI: 10.1016/j.jat.2005.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A Riemann–Hilbert approach to some theorems on Toeplitz operators and orthogonal polynomials

Abstract: This paper is dedicated to Barry Simon on the occasion of his 60th birthday in appreciation for all that he has taught us. AbstractIn this paper, the authors show how to use Riemann-Hilbert techniques to prove various results, some old, some new, in the theory of Toeplitz operators and orthogonal polynomials on the unit circle (OPUCs). There are four main results: the first concerns the approximation of the inverse of a Toeplitz operator by the inverses of its finite truncations. The second concerns a new proo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…This result is due to Deift-Ostensson [4], but [12] has a new proof. Earlier, [10] proved the weaker result when R 3 is replaced by R 2 .…”
Section: Remarksmentioning
confidence: 84%
See 1 more Smart Citation
“…This result is due to Deift-Ostensson [4], but [12] has a new proof. Earlier, [10] proved the weaker result when R 3 is replaced by R 2 .…”
Section: Remarksmentioning
confidence: 84%
“…The main theorems of [12] are: Theorem 1.3 [4]. If lim sup|α n | 1/n = R −1 < 1, then r(z) − S(z) is analytic in {z : 1 − δ < |z| < R 3 } for some δ > 0.…”
Section: The Jacobi Parameters Have a Complete Asymptotic Expansion Imentioning
confidence: 99%
“…An important fact, established independently in [2,13,8] (cf. Corollary 2 therein) is that for n ∈ N,…”
Section: Corollarymentioning
confidence: 95%
“…Simon [18] proved that r(z) -S(z) is analytic in {z I 1 -E < Izi < R2} when (3.1) holds, thereby generalizing [1]. The ultimate result of this genre was found independently by Deift-Ostensson [7] and Martinez-Finkelshtein et al [13]; an alternate proof was then found by Simon [20].…”
Section: Theorem 32 ([6]mentioning
confidence: 98%